Modelling the Thin-Layer Drying Kinetics of Marinated Beef during Infrared-Assisted Hot Air Processing of Biltong - Francis C. Muga; Moses O. Marenya; Tilahun S. Workneh (International Journal of Food Science)
Biltong is a dried meat product that is widely consumed in South Africa. The marinated meat is traditionally dried under ambient winter conditions while commercial biltong producers use hot air driers. Hot air drying is time-consuming and energy-intensive. A combined infrared and hot air drying (IRHAD) is an alternative method of drying meat during biltong processing. The aim of this study was to establish the effect of the infrared (IR) power, the temperature, and velocity of the drying air on the drying kinetics of marinated beef and subsequently select the best thin-layer drying model for IRHAD during biltong processing. Marinated beef samples were dried at IR power levels of 500, 750, and 1000 W; drying air temperatures of 30, 35, and 40°C; and air velocity of 1.5 and 2.5 m∙s-1. Results indicate that increasing the IR power and the drying air temperature increased the IR emitter temperature and the core temperature of the marinated beef sample. Consequently, increasing the drying rate thus reduced drying time. The air velocity had an inverse relationship with the IR emitter temperature, the core temperature of the marinated beef sample, and the drying rate. The drying process was characterised by a rising rate period in the first half an hour, followed by a falling rate period which implies that moisture transport occurred partly by surface evaporation and predominantly by diffusion. The effective moisture diffusivity ranged from 4.560×10−10 to 13.7×10−10 m2∙s−1, while, the activation energy ranged between 40.97 and 59.16 kJ∙mol-1. The IRHAD of marinated beef during its processing to biltong was best described by the two-term model since it had the highest R2 (0.9982-0.9993) and the lowest RMSE (0.0062-0.0099). The power level of the IR emitter of 1000 W combined with a drying air temperature and velocity of 40°C and 1.5 m∙s-1, respectively, showed the highest improvement in the drying kinetics and the lowest drying time of 5.61±0.35 hours; hence, it is recommended as a possible drying alternative for the processing of biltong.